Magnesium(II) and Calcium(II) Complexes of Some Schiff Bases - Rao, T.V.R.K.; Das, B.N. (Asian Journal of Chemistry, 2010)
Magnesium(II) and calcium(II) complexes of some Schiff bases, viz., salicylidene p-toluidine, salicylidene sulphanilic acid, vanilidene p-toluidine or vanilidene sulphanilic acid have been synthesized and characterised.